2014
DOI: 10.3109/10428194.2014.919634
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 + T cell recruitment to the skin in mycosis fungoides: potential contributions by thymic stromal lymphopoietin and interleukin-16

Abstract: Mycosis fungoides (MF) is characterized by skin accumulation of CCR4+CCR7- effector memory T cells; however the mechanism for their recruitment is not clearly identified. Thymic Stromal Lymphopoietin (TSLP) is a keratinocyte-derived cytokine that triggers Th2 immunity and is associated with T cell recruitment to the skin in atopic dermatitis. Interleukin-16 (IL-16) is a chemoattractant and growth factor for CD4+T cells. We hypothesized that TSLP and IL-16 could contribute to recruitment of malignant T cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
(2 reference statements)
2
22
0
2
Order By: Relevance
“…However, similar to CXCL9 and CXCL10, the expression of CXCR3 also decreases during disease progression, which is accompanied by a gradual loss of epidermotropism [12, 13, 45]. In contrast, CCR4, the receptor for CCL17 and CCL22, is continuously expressed by the malignant T cells and, in line with the upregulation of CCL17 and CCL22, the number of CCR4-positive T cells increases in later disease stages [10, 47, 49]. A recent phase I/II clinical study of the humanized anti-CCR4 antibody, mogamulizumab, showed promising results in heavily pretreated patients, supporting an important role of the CCR4-CCL17/CCL22 axis in the pathogenesis of CTCL [54].…”
Section: Changes In the Chemokine Profile Facilitate The Development mentioning
confidence: 99%
See 2 more Smart Citations
“…However, similar to CXCL9 and CXCL10, the expression of CXCR3 also decreases during disease progression, which is accompanied by a gradual loss of epidermotropism [12, 13, 45]. In contrast, CCR4, the receptor for CCL17 and CCL22, is continuously expressed by the malignant T cells and, in line with the upregulation of CCL17 and CCL22, the number of CCR4-positive T cells increases in later disease stages [10, 47, 49]. A recent phase I/II clinical study of the humanized anti-CCR4 antibody, mogamulizumab, showed promising results in heavily pretreated patients, supporting an important role of the CCR4-CCL17/CCL22 axis in the pathogenesis of CTCL [54].…”
Section: Changes In the Chemokine Profile Facilitate The Development mentioning
confidence: 99%
“…IL-16 is a growth factor and a chemo-attractant for CD4 + T cells. Accordingly, evidence supports that elevated levels of IL-16 contribute to the cutaneous accumulation of the malignant T cells by augmenting their intradermal proliferation and potentiating their recruitment into the skin [49, 69]. The expression of IL-17A and IL-17F is heterogeneous and confined to a subset of patients which is likely the cause of discrepant reports regarding their expression in CTCL [55, 62, 7073].…”
Section: The Expression Of Pro-tumorigenic Cytokines Increases Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…The three Hodgkin lymphoma patients and the mycosis fungoides patient developed progressive neurological deterioration and died soon after the development of the PML [53 & ]. Chemokine receptor 4 (CCR4) is expressed by T cells and is important for their recruitment to the skin [54]. Mogamulizumab is a monoclonal antibody against CCR4 that has been developed for the treatment of diverse hematological malignancies and asthma [55].…”
Section: The European Organization For Research and Treatment Of Cancermentioning
confidence: 99%
“…5 Recently, the association of thymic stromal lymphopoietin (TSLP) with tumor survival and progression of several kinds of tumors, such as breast, lung, gastric, pancreatic, and cervical cancers, and mycosis fungoides have been reported. [10][11][12] The TSLP receptor (TSLPR) complex has also been found in pediatric B-cell acute lymphocytic leukemia. 10 Although TSLPR expression is observed in multiple myeloma cell lines, TSLP does not affect the proliferation or drug resistance of multiple myeloma cells.…”
Section: Detection Of Minimal Bone Marrow Involvement Of Blastic Plasmentioning
confidence: 99%